Handwriting Recognition Methods and Approaches - Bodnia, Yevhen; Kozulia, Mariia (My University, 2020)
The paper analyzes the existing methods and approaches for character recognition. The subject area and its problems are considered. The best method for solving the handwriting recognition task is the convolutional neural network method. Features of software implementation of convolutional neural network, implementation of data storage model for training are considered.
Keywords: character recognition; neural network; recognition methods; convolutional network; data models